Ideas on municipalities, chaos theory and transformational leadership - (:unkn) unknown (Springer, 2014)
Socio-economic developments as well as developments in information and transportation technologies have transformed the world to a big city. The concept of globalization on the one hand homologised cultures to each other, and on the other hand facilitated the provision of local values into global markets and strengthened locality phenomenon. This situation has increased local authorities’ awareness of international relations and global developments. Many local authorities put tremendous endeavour to have a voice in an international and even global area. Having long been under the influence of in-house and local variables and parameters, local authorities for several decades have been in a position where they need to take into consideration international and global parameters. Local authorities need to tackle challenges in a sort of chaos that has been caused by the current exceptional ever-changing and competitive environment. Chaos theory can be an effective tool in explaining developments and settling the conflicts in the today’s world. Municipalities – the most advanced type of local authority in Turkey, have been structured according to “strong presidency” model. Mayor has been granted significant power in this system, which in turn moved mayor into a sort of political leadership position in the context of both internal structure of the municipality and the city government. In order for the cities in developing countries such as Turkey to obtain strong positions in the globalizing world, a consistent leadership at the outset must be exhibited in municipal administration. Transformational leadership approach developed in the last quarter of the twentieth century can be used in this sense. This approach shows similar features to those that of chaos theory as well as can provide the leadership requirements needed by “strong presidency” model. © Springer Science+Business Media Dordrecht 2014.
Keywords: Chaos theory; Civil society organization; Executive committee; Legal personality; Transformational leadership